2016
DOI: 10.1007/s11356-016-7998-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of total mercury and methylmercury around the small-scale gold mining area along the Cikaniki River, Bogor, Indonesia

Abstract: This study investigates the distribution of total mercury (T-Hg) and methylmercury (MeHg) in the soil and water around the artisanal and small-scale gold mining (ASGM) area along the Cikaniki River, West Java, Indonesia. The concentration of T-Hg and MeHg in the forest soil ranged from 0.07 to 16.7 mg kg and from <0.07 to 2.0 μg kg, respectively, whereas it ranged from 0.40 to 24.9 mg kg and from <0.07 to 56.3 μg kg, respectively, in the paddy field soil. In the vertical variation of the T-Hg of forest soil, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
2
22
1
1
Order By: Relevance
“…Most mercury enters the water body via anthropogenic activities, mainly industrial waste and illegal gold mining (Purnawan et al, 2017;Juhaeti et al, 2017). There are several rivers in Indonesia that have been reported to be contaminated with mercury including the Kuantan River, Riau (Yulis, 2018), the Banyuasin River, South Sumatra (Suteja et al, 2019), the Banyumas River, Central Java (Budianta et al, 2019) and the Cikaniki River, Bogor (Tomiyasu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most mercury enters the water body via anthropogenic activities, mainly industrial waste and illegal gold mining (Purnawan et al, 2017;Juhaeti et al, 2017). There are several rivers in Indonesia that have been reported to be contaminated with mercury including the Kuantan River, Riau (Yulis, 2018), the Banyuasin River, South Sumatra (Suteja et al, 2019), the Banyumas River, Central Java (Budianta et al, 2019) and the Cikaniki River, Bogor (Tomiyasu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the weak regulatory regime is worsened by inconsistent lawenforcement regarding, e.g. illegal Mercury distribution and use (Ismawati, 2014;Tomiyasu et al, 2017), environmental abuse and pollution (Nainggolan, 2015;Nopriadi, 2016;Resosudarmo et al, 2009) and IGM operations (Nainggolan, 2015;Nopriadi, 2016). After observing these problems for many years, Labonne (2014, p. 1) concluded that governments and investors have little interest in supporting ASM, and that "ASM's primary concerns are sidelined by the agenda of other stakeholders" who have access to power.…”
Section: Regulations and Policiesmentioning
confidence: 99%
“…Indonesian artisanal and small-scale gold mining activities (ASGM) have been found in the islands of Borneo (Kalimantan), Buru, Sulawesi, Java and operations extending to the islands of Lombok and Sumbawa (Krisnayanti et al 2012;Male et al 2013;Tomiyasu et al 2016). In the ASGM, gold is recovered by miners through a two-stage process of whole-ore amalgamation and cyanidation.…”
Section: Introductionmentioning
confidence: 99%